2020
DOI: 10.3389/fnins.2020.00497
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional vs. Cognitive Intelligence in Economic Decision-Making Amongst Older Adults

Abstract: The links between emotions, bio-regulatory processes, and economic decision-making are well-established in the context of age-related changes in fluid, real-time, decision competency. The objective of the research reported here is to assess the relative contributions, interactions, and impacts of affective and cognitive intelligence in economic, value-based decision-making amongst older adults. Additionally, we explored this decision-making competency in the context of the neurobiology of aging by examining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 109 publications
(115 reference statements)
0
17
0
Order By: Relevance
“…While this region is a primary sensory cortex, it has bi-directional connections with the insula, primary and association sensory cortices, and perhaps serves as an integrated hub of somatic marker activity that informs CDM. Recent structural imaging research has suggested that the cortical thickness of the auditory cortex predicts IGT score, especially learning across blocks from start to finish in the task [41]. This research [41], tapped older adults who may be impaired in CDM, as would psychiatric patients, suggesting that the auditory cortex hub of somatic marker information may play a critical role in both brain reward and DAN networks in real-life and ecologically valid decision-making measures.…”
Section: Plos Onementioning
confidence: 90%
“…While this region is a primary sensory cortex, it has bi-directional connections with the insula, primary and association sensory cortices, and perhaps serves as an integrated hub of somatic marker activity that informs CDM. Recent structural imaging research has suggested that the cortical thickness of the auditory cortex predicts IGT score, especially learning across blocks from start to finish in the task [41]. This research [41], tapped older adults who may be impaired in CDM, as would psychiatric patients, suggesting that the auditory cortex hub of somatic marker information may play a critical role in both brain reward and DAN networks in real-life and ecologically valid decision-making measures.…”
Section: Plos Onementioning
confidence: 90%
“…Due to the time limitations, social awareness is not considered in this study; it might be taken in future studies [4]. When it comes to making decisions regarding any business, usually, one may believe that an older, more experienced person can make a better decision because he knows more than a young person who has just entered the market, many years after the former [24]. The authors in [24] argue that this is not the case because an older person can have less emotional control than a young person.…”
Section: Literature Review and Theoretical Conceptualization 21 Operational Emotional Intelligencementioning
confidence: 99%
“…When it comes to making decisions regarding any business, usually, one may believe that an older, more experienced person can make a better decision because he knows more than a young person who has just entered the market, many years after the former [24]. The authors in [24] argue that this is not the case because an older person can have less emotional control than a young person. Hence, the odds of making a better decision are with a young person with more emotional intelligence and control.…”
Section: Literature Review and Theoretical Conceptualization 21 Operational Emotional Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Studies using hierarchical regression for IGT performance explain a modest proportion of IGT decision-making because IGT is a complex task with considerable heterogeneity (large standard deviations; Bowman and Turnbull, 2003 ; Newman et al, 2008 ; Singh and Khan, 2009 ; Singh, 2013a , b ). For example, measures of emotional and cognitive intelligence explained 12% of IGT choices (adjusted R 2 = 0.12; Ramchandran et al, 2020 ), personality explained 10% of the IGT choices ( R 2 = 0.10 for males and 0.05 for females; Hooper et al, 2008 ), and heart rate explained 19% of male IGT decision-making in the risk phase ( Wemm and Wulfert, 2017 ).…”
Section: Limitations and Conclusionmentioning
confidence: 99%